Electric Mosquito Repellent Effect of Male Breadfruit Flower Mat Causes Mosquito Mortality Anopheles sp. - Moniharapon, Debby Dijola; Kaihena, Martha; Unitly, Adrien Jems Akiles (Devotion : Journal of Research and Community Service, 2023)
Through mosquito bites, parasites of the genus Plasmodium spread the disease known as malaria. Malaria-carrying mosquitoes of the genus Anopheles sp. One secure method of controlling the Anopheles sp. mosquito population is biological mosquito control. Since the biological method does not use chemicals but rather the phytochemicals found in plants, one of which contains compounds from the male breadfruit flower and is capable of acting as a vegetable larvicide or mosquito repellent. The aims of the study is to evaluate the effectiveness of electric mosquito mats that contain male breadfruit flowers to kill or cause mosquitoes (Anopheles sp.) to die. A completely randomized design (CRD) was used for the experiment. The results showed a change in the mortality of Anopheles sp. mosquito larvae. After exposure to breadfruit flower mat doses of 0.5gr, 1gr, 1.5gr, 2gr compared to no administration. Thus, it was concluded that male breadfruit flower mats with concentrations of 0.5gr, 1gr, 1.5gr, and 2gr had an insecticidal effect on the mortality of Anopheles sp. mosquitoes. with an effective concentration of 2gr (96.5% mortality), of which 50% mortality (LC50) of Anopheles sp. larvae. Occurred at a concentration of ethanol extract of male breadfruit flowers dose 0.36gr.